Methods of grouping learners at school - Dupriez, Vincent; Unesco; International Institute for Educational Planning (Paris UNESCO, International Institute for Educational Planning, 2010)
"How should classrooms be formed in a school? What criteria should be used for dividing students up between schools and classes? When is tracking/streaming and ability grouping appropriate in a school system? This book addresses each of these questions without proposing a definitive reply. The author reviews the research of the past decade in order to evaluate the impact of class composition on students? learning."--Back cover.
Uniform or mixed ability classes? -- Segregation among schools -- Integrated or differentiated education systems?
Keywords: Ability grouping in education; Education, Cooperative; Educational innovations